Individualized Colorectal Cancer Screening Discussions Between Older Adults and Their Primary Care Providers: A Cross-Sectional Study. Issue 1 (April 2018) - Kistler, Christine E.; Golin, Carol; Sundaram, Anupama; Morris, Carolyn; Dalton, Alexandra F.; Ferrari, Renee; Lewis, Carmen L.
Introduction. Discussions of colorectal cancer (CRC) screening with older adults should be individualized to maximize appropriate screening. Our aim was to describe CRC screening discussions and explore their associations with patient characteristics and screening intentions.Methods. Cross-sectional survey of 422 primary care patients aged ≥70 years and eligible for CRC screening, including open-ended questions about CRC screening discussions. Primary outcomes were the frequency with which CRC screening discussions occurred, who had those discussions, and the domains that emerged from thematic analysis of participants' brief reports of their discussions. We also examined the associations between 1) patient characteristics and whether a screening discussion occurred and 2) the domains discussed and what screening decisions were made.Results. Of 422 participants, 209 reported having discussions and 201 responded to open-ended questions about CRC discussions. In a regression analysis, several factors were associated with increased odds of having a discussion: participants' preference to pursue screening (odds ratio [OR] 2.3, 95% confidence interval [CI] 1.3, 3.9), good health (OR 2.9, 95% CI 1.7, 4.8), and receipt of the decision aid (OR 2.1, 95% CI 1.4, 3.2). Our thematic analysis identified five domains related to discussion content and three related to discussion process. The CRC screening–related information domain was the most commonly discussed content domain, and the timing/frequency domain was associated with increased odds of intent to pursue screening. Decision-making role, the most commonly discussed process domain, was associated with increased odds of the intent to forgo CRC screening.Conclusions and Relevance. CRC screening discussions varied by type of participant and content. Future work is needed to determine if interventions focused on specific domains alters the appropriateness of participants' colorectal cancer screening intentions.